ИССЛЕДОВАНИЕ И РАЗРАБОТКА МОБИЛЬНОГО ШАГАЮЩЕГО РОБОТА - Batyrkhan, З.А.; Dikambai, Н.Б.; Sydykhov, Б.Д. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The inventing of teaching methods to the educational process at school is determined by the fact that each teacher or curriculum developer strives to ensure that his concepts of teaching and the formation of teaching principles are most effectively implemented in the educational environment. Such forms of interaction determine that each teacher or professor tries to integrate and invent the practical elements of the the chosen subject into the educational process both in the form of choose structures and in the form of formalized complex forms of education. This study is aimed at teaching robotics with the special developed robot and the interface which is built to control and give commands to the robot. The analysis of the previously acquired knowledge and skills shows that teaching methods of robotics to elementary school students has faced with difficulties. The collected information of the pedagogical experiment generally confirmed the hypothesis of the obtained research. If to invent a unique system of robotics subject, forms and development methods of the elementary school students’ robotics design skills to robotic design and solution of tasks and practical assignments based on the giving commands and controlling walking robot via special built interface, then it will contribute to the increase in the effectiveness of the robotic design teaching, the formation of the students’ ideas of the model nature of cognition, and the development of their cognitive and creative abilities. The obtained results show that controlling robot via special interface contributes to the increase in the level of the elementary school students’ robotics design skills by each particular criteria, which proves that it makes easier the way of teaching robotics subject to the students of elementary school.